2023
DOI: 10.18291/njwls.136521
|View full text |Cite
|
Sign up to set email alerts
|

Working with Robotic Animals in Dementia Care: The Significance of Caregivers’ Competences

Abstract: Robotic animals are increasingly discussed as a solution to challenges connected to the aging population and limited resources in care. While previous research focuses on the robots’ effect on the patients’ well-being, there is a general lack of knowledge regarding the hands-on experience of caregivers’ use of robots. Therefore, the aim of the study is to explore the competences that caregivers draw upon when facilitating interaction between residents and robots. The study was conducted through ethnographic ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Therefore, the staff played a crucial role in identifying agitation and using the companion robot as an active caring intervention. A recent study showed that care staff's work with companion robots requires embodied, social, and ethical competence (M. Persson et al, 2023), which is in line with the results of our work.…”
Section: Impact On Staff's Practicessupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, the staff played a crucial role in identifying agitation and using the companion robot as an active caring intervention. A recent study showed that care staff's work with companion robots requires embodied, social, and ethical competence (M. Persson et al, 2023), which is in line with the results of our work.…”
Section: Impact On Staff's Practicessupporting
confidence: 91%
“…their care was mediated through the robot by providing a distraction that they themselves had a hard time offering. The observations presented in the thesis have also been seen in a recent study that discussed how care staff's work with companion robots requires embodied, social, and ethical competence (M. Persson et al, 2023). Regarding the ethical concerns raised by several roboethicist (e.g.…”
Section: How Does the Use Of Companion Robots Affect Care Staff's Pra...mentioning
confidence: 54%
See 1 more Smart Citation
“…In this paper we adopt a relational approach which involves understanding the residents’ use of robot animals in social situations that encompass material objects and other social subjects ( Robinson et al, 2016 ; DeFalco, 2020 ). Previous studies have shown that social robots demand involvement from care workers to engage users ( Chevallier, 2022 ; Persson et al, 2023 ). For instance, the care staff may need to participate in conversations ( Chang and Šabanović, 2015 ) to ensure that the robot is accessible at the right moment ( Jung et al, 2017 ; Moyle et al, 2018 ), and to “stage” it by carrying it in a particular manner, discussing it, and sometimes physically guiding users on how to handle it ( Pfadenhauer and Dukat, 2015 ).…”
Section: Studying Robots In Social Contextmentioning
confidence: 99%
“…In this regard, studies have shown how robot animals can serve as an “icebreaker” between staff and residents, with staff members often “joking and laughing” with residents about the robot ( Robinson et al, 2016 ). However, Chevallier (2022) also shows that forceful attempts to engage residents, including physical cues, can backfire and result in annoyance and anger (see also Persson et al, 2024 ).…”
Section: Studying Robots In Social Contextmentioning
confidence: 99%